Reconstructionism of Qur'anic Education in a Love-Based Curriculum with a Deep Learning Approach - Mariatul Hikmah; Wiwied Widiyanti; Isnaini Septemiarti (Pascasarjana IAI Diniyyah Pekanbaru, 2026)
This study aims to analyze the existence of Qur'anic Education through the application of a deep learning approach that is examined based on reconstructionist studies. The research method used is a qualitative approach supported by primary data in the form of document manuscripts, interview results, and content and material analysis from various academic activities such as seminars, workshops, and training related to the implementation of a love-based curriculum. The research subjects include madrasah teachers and students involved in the implementation of a love-based curriculum. The novelty in this study lies in the implementation of a love-based curriculum in Qur'anic Education that is designed based on a deep learning approach within the framework of the philosophy of reconstructionism. This approach is realized through curriculum reconstruction that is adapted to the dynamics of developments in the era, including the integration of new technologies and cultures, without ignoring the foundation of Qur'anic values. The results of the study indicate that the application of a love-based curriculum can strengthen the formation of students' character through exemplary behavior (uswatun hasanah) and habituation that are internalized in the learning process at school.